The Use of Cyber Counseling to Improve Excellent Personality in Students in Indonesia - Mayang Dita Utami; Ulfa Khairunnisa; Gusman Lesmana (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research discusses the importance of implementing cyber counseling as an alternative in forming superior personalities in students in Indonesia. Currently, some students experience difficulties in developing their self-concept and character. One reason is the lack of access to effective counseling services and the stigma associated with consulting face-to-face counselors. Therefore, cyber counseling is an attractive solution because it can provide support and guidance online, reduce embarrassment and facilitate a positive personality.